Barriers to Enrollment of National Health Insurance Scheme in Uttargaya Rural Municipality, Rasuwa - Neupane, Pradip; Mandawi Subedi; Jenisha Khadka; Sabita Budh Thapa; Ram Krishna Shahi (MultiTech Publisher, 2024)
The Social Health Security Program (SHSP) is a social protection program of the Government of Nepal that aims to enable all citizens to access quality and effective healthcare services without any financial burden. A cross-sectional household-based and quantitative in-nature study was conducted in Rasuwa district. This study's population was residents of Uttargaya rural municipality wards no 4 and 5. How different factors are related to SHI enrolment. Ethnicity (p=<0.001), religion (p=<0.001), IWI grade (p=0.010), know about health insurance (p=<0.001), the behavior of service providers (p=<0.001), neighbors enrollment (p=<0.001), discussed SHI with neighbors (p=0.001), and family members agreed to enroll (p=0.002) were significantly associated with enrollment in SHI whereas others factors did not show any significant association with enrollment in social health insurance. This study found that enrollment was significantly associated with different independent variables. Poor knowledge of SHI, unfriendly behaviors of service providers, lack of trust, and unaffordability of premium costs were identified as barriers. Furthermore, Inappropriate timing of premium collection, limited services point, feeling that enrollment was not necessary, long queue, inadequate number of enrollment assistant and mandatory refer card were also reasons for not enrolling in SHI.